Disruption of Epidermal Growth Factor Receptor but Not EGF Blocks Follicle Activation in Zebrafish Ovary - Song, Yanlong; Chen, Weiting; Zhu, Bo; Ge, Wei (Frontiers in Cell and Developmental Biology, 2022)
Folliculogenesis is controlled by intimate communications between oocytes and surrounding follicle cells. Epidermal growth factor (EGF/Egf) is an important paracrine/autocrine factor in vertebrate ovary, and it is well known for its stimulation of oocyte maturation. However, the role of EGF signaling through its receptor (EGFR/Egfr) in ovarian folliculogenesis is poorly understood, especially at early stages of follicle development. In this study, we created zebrafish mutants for Egf (egf−/−) and Egfr (egfra−/− and egfrb−/−) by CRISPR/Cas9 technique. Surprisingly, these mutants all survived well with little abnormality in growth and development. Spermatogenesis and folliculogenesis were both normal in egf−/− males and females. Their fecundity was comparable to that of the wildtype fish at 4 months post-fertilization (mpf); however, the fertilization rate of mutant eggs (egf−/−) decreased significantly at 7 mpf. Interestingly, disruption of egfra (egfra−/−) led to failed follicle activation with folliculogenesis being blocked at primary–secondary growth transition (PG-SG transition), leading to female infertility, whereas the mutant males remained fertile. The mutant ovary (egfra−/−) showed abnormal expression of a substantial number of genes involved in oxidative metabolism, gene transcription, cytomembrane transport, steroid hormone biosynthesis, and immune response. The stunted PG oocytes in egfra−/− ovary eventually underwent degeneration after 6 months followed by sex reversal to males with functional testes. No abnormal phenotypes were found in the mutant of truncated form of EGFR (egfrb). In summary, our data revealed critical roles for EGFR signaling in early folliculogenesis, especially at the PG-SG transition or follicle activation.